2008
DOI: 10.1007/s00520-008-0475-4
|View full text |Cite
|
Sign up to set email alerts
|

Scalp cooling to prevent chemotherapy-induced hair loss: practical and clinical considerations

Abstract: Chemotherapy-induced hair loss is perceived as burdensome. It may be prevented by offering scalp cooling which is often an effective method to prevent this form of hair loss and is tolerated well by patients. However, if possible, scalp-cooling techniques should be improved and their effectiveness should be increased because if scalp cooling is unsuccessful, patients' rate their hair loss as more burdensome compared to noncooled patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 32 publications
(32 reference statements)
3
68
0
7
Order By: Relevance
“…In all cases, epirubicin was combined with cyclophosphamide (500 or 600 mg/m2). Mols et al (2009) found for different adjuvant CT-regimens, that breast cancer patients who did not receive SC reported average hair loss VAS 85 (range 9 to 100), where 100 is complete hair loss. This supports the common experience that current (neo-)adjuvant CT for breast cancer is causing complete alopecia in almost all cases.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, epirubicin was combined with cyclophosphamide (500 or 600 mg/m2). Mols et al (2009) found for different adjuvant CT-regimens, that breast cancer patients who did not receive SC reported average hair loss VAS 85 (range 9 to 100), where 100 is complete hair loss. This supports the common experience that current (neo-)adjuvant CT for breast cancer is causing complete alopecia in almost all cases.…”
Section: Discussionmentioning
confidence: 99%
“…46 The efficacy of scalp cooling has been investigated in 7 randomized clinical studies, 6 of which found cooling to be effective with varying degrees of success. 47 A recent prospective multicenter study found cooling to be effective in approximately 50% of patients. 47 An earlier review of the literature determined the average success rate in studies from 1995 onward was 73%.…”
Section: Physical Interventionsmentioning
confidence: 98%
“…47 A recent prospective multicenter study found cooling to be effective in approximately 50% of patients. 47 An earlier review of the literature determined the average success rate in studies from 1995 onward was 73%. 48 The variation in outcome likely depends on a number of factors including the type of chemotherapy used, cooling method, duration of cooling time, and degree of hypothermia.…”
Section: Physical Interventionsmentioning
confidence: 98%
“…Temporary chemotherapy-induced alopecia, one of the most common and distressing side effects of chemotherapy treatment, can lead to a negative body image, lower self-esteem, sexual impairment, severe depression, anxiety, and disturbances in social relationships 2 . Fear of hair loss and the associated distress can even result in refusal to undergo appropriate chemotherapy treatment 3 .…”
Section: Introductionmentioning
confidence: 99%